2016
DOI: 10.1002/tea.21370
|View full text |Cite
|
Sign up to set email alerts
|

Learned inequality: Racial labels in the biology curriculum can affect the development of racial prejudice

Abstract: For over a century, genetic arguments for the existence of racial inequality have been used to oppose policies that promote social equality. And, over that same time period, American biology textbooks have repeatedly discussed genetic differences between races. This experiment tests whether racial terminology in the biology curriculum causes adolescents to develop genetic beliefs about racial difference, thereby affecting prejudice. Individual students (N = 135, grades 7–9) were randomly assigned within their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
102
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 93 publications
(225 reference statements)
0
102
0
Order By: Relevance
“…Furthermore, our race interventions used these same representations to help students learn about genetic variation. Although a visual approach to representing genetic variation is common in population genetics research (Donovan, ), the representations of variation that we used in our study do not appear to be a common component of teaching about genetic variation. Instead, students tend to learn models of genetic variation with numbers (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our race interventions used these same representations to help students learn about genetic variation. Although a visual approach to representing genetic variation is common in population genetics research (Donovan, ), the representations of variation that we used in our study do not appear to be a common component of teaching about genetic variation. Instead, students tend to learn models of genetic variation with numbers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A principal components analysis supplemented with a parallel analysis demonstrated that these two item types, between and within items, were statistically discriminable (see Supporting Information). As in previous studies (Donovan, ), we averaged the between race and within race questions separately. Then, we applied Equation to these data, which yielded a single proportion for each student that could take on any value between 0 and 1.…”
Section: Methodsmentioning
confidence: 99%
“…Racial essentialists believe that: (a) biology causes people of different races to be physically, cognitively, and behaviorally different; and (b) same race individuals are physically, cognitively, and behaviorally uniform (Andreychik & Gill, ). Those who combine these beliefs with the assumption that biologically influenced abilities are immutable often argue that it is pointless to intervene socially to reduce racial inequality in society (Donovan, ). Today we know that racial essentialism is not supported by scientific studies of human variation (Donovan, , ).…”
mentioning
confidence: 99%
“…New experimental research has demonstrated a cause‐effect relationship between the treatment of race in the biology curriculum and the development of racial essentialism (Donovan, , , ). When students learn about the prevalence of sickle cell anemia in Sub‐Saharan African populations or the prevalence of cystic fibrosis in Northern‐European populations in middle or high school biology classes it can unintentionally cause youth to perceive more genetic variation between races than actually exists (Donovan, ) and to infer that racial groups differ in intelligence for genetic reasons (Donovan, , , ).…”
mentioning
confidence: 99%
See 1 more Smart Citation